O MAIS DO MESMO NO TELEJORNALISMO DIÁRIO: O PROCESSO DE REPETIÇÃO EM REPORTAGENS DE TV SOBRE DATAS COMEMORATIVAS E TEMAS RECORRENTES - Rumor, Vanessa (2016)
The newspaper is linked to the production routines. They participate in the process that makes the news may be constituted as such. And in the midst of construction processes of a report, it appears to repeat, be it on the subject, the information in ways that is formatted. This repetition in television journalism is a recurring phenomenon due to several factors, but becomes more common when it comes to reporting on special dates and events that repeat in a given period of time. The development of this dissertation sought to point out where, how and in what way this repetition occurs in TV news, as well as what are the factors that interfere in this process. The understanding of these issues occurred with the construction of a methodological approach that linked the literature, research focused especially to the theories underlying the debated journalistic logic, the TV materials of content analysis on holidays and events held in the years 2014 and 2015 for a TV station of the city of Ponta Grossa, and also interviews with professionals involved in the process to trace the characteristics of how they understand what to do differently in television journalism with the repetition of evidence. The analysis showed that, among other reasons, the internal rules of writing, the short time for the production of materials and the automated make are some of the main reasons that lead to the emergence of the phenomenon addressed in this research.